Imported Chikungunya fever case in Greece in June 2014 and public health response. (17th February 2016) - Tsiodras, Sotirios; Pervanidou, Danai; Papadopoulou, Elpida; Kavatha, Dimitra; Baka, Agoritsa; Koliopoulos, George; Badieritakis, Evangelos; Michaelakis, Antonios; Gavana, Elpida; Patsoula, Eleni; Tsimpos, Ioannis; Gioksari, Thalia; et al.
Abstract : We report about the first imported case of Chikungunya fever in Greece in a Greek traveler returning from the Dominican Republic and the associated public health response. We investigated the case and performed focused epidemiological and entomological investigation in all areas the patient visited during the infectious period, to identify the targeted interventions needed. Entomological investigation revealed the occurrence of the competent vector Aedes albopictus (Diptera: Culicidae) in the environment surrounding the hospital where the patient was admitted and in her workplace. All captured mosquitoes tested negative for Chikungunya virus. We further conducted clinical and laboratory examination of the patient's co-travelers, gave advice on appropriate personal preventive measures against mosquito bites to the patient and co-travelers and on vector control, and raised awareness among health professionals throughout Greece. The risk of introduction and local transmission of Chikungunya and other arboviruses in Greece and other European countries is present, as the competent vector exists in many parts of Europe. Public health professionals, travel medicine specialists and clinicians should maintain awareness regarding this possibility of importation of arbovirus cases in order to provide the appropriate advice, seek the prompt diagnosis, and implement appropriate interventions. Mobilization of various stakeholders will lead to enhanced epidemiological and entomological surveillance that will allow for improved risk assessment in each area.